(untitled) (Prilozi za orijentalnu filologiju, 2025)
This paper explores traces of first–person narrative in the writings of the Balkan Ottoman author Münīrī–i Belġrādī1 (d. ca 1620–1628). Based on the available data, it is known that he held the positions of mufti, müderris, and Sufi scholar. It is therefore probable that he also served as a sheikh of a Sufi order, most likely the Halveti order. Münīrī–i Belġrādī was active during the second half of the sixteenth century and the early decades of the seventeenth century, primarily in Belgrade. Through close textual analysis of his writings, the study contributes to ongoing discussions about the rhetorical construction of selfhood in Ottoman manuscript culture. Rather than treating the first–person singular pronoun “I” as the sole marker of ego–narrative, the paper identifies and interprets indirect and periphrastic strategies for articulating the self. Such texts offer not only rhetorical complexity but also valuable historical insights, particularly in terms of factual content. The study argues that representation and factuality in these writings are not mutually exclusive, but rather interwoven dimensions of Ottoman literary expression. Researchers approaching ego–narrative in this context should attend to both rhetorical strategies and the historical realities embedded within them.